PENINGKATAN KEBUGARAN JASMANI MELALUI PROGRAM LATIHAN JALAN CEPAT - Candra Kurniawan; Herman Tarigan; Suranto Suranto (JUPE (Jurnal Penjaskesrek), 2013)
This study was conducted to determine the results of improvement of physical fitness through fast walking exercise program on fifth grade students of SD Negeri 1 Kedaton Bandar Lampung, and to know the results of the different levels of physical fitness of students who take brisk workout program after giving treatment for 4 weeks for 5 times weekly meetings with students who do not follow the fast walking training program. There are differences in the calculation of the results of improvement of physical fitness among students who were given treatment (experimental group) was 34.30%, and untreated (control group) of 0.73%. Use of fast walking exercise program is very effective in improving physical fitness in the fifth grade students of SD Negeri 1 Kedaton Bandar Lampung.Penelitian ini dilakukan dengan tujuan untuk mengetahui hasil peningkatan kebugaran jasmani melalui program latihan jalan cepat pada siswa kelas V SD Negeri 1 Kedaton Bandar Lampung, serta mengetahui hasil perbedaan tingkat kebugaran jasmani siswa yang mengikuti program latihan jalan cepat setelah pemberian perlakuan selama 4 minggu sebanyak 5 kali pertemuan perminggu dengan siswa yang tidak mengikuti program latihan jalan cepat. Dari hasil perhitungan terdapat perbedaan hasil peningkatan kebugaran jasmani antara siswa yang diberi perlakuan (kelompok eksperimen) sebesar 34,30 persen, dan yang tidak diberi perlakuan (kelompok kontrol) sebesar 0,73 persen. Penggunaan program latihan jalan cepat sangat efektif dalam meningkatkan kebugaran jasmani pada siswa kelas V SD Negeri 1 Kedaton Bandar Lampung.Kata kunci : peningkatan, kebugaran jasmani, program latihan jalan cepat